Experimental determination and theoretical framework of kinetic fractionation at the water vapour–ice interface at low temperature. (1st February 2016) - Casado, Mathieu; Cauquoin, Alexandre; Landais, Amaelle; Israel, Dan; Orsi, Anaïs; Pangui, Edouard; Landsberg, Janek; Kerstel, Erik; Prie, Frederic; Doussin, Jean-François
Abstract: Water isotopes are commonly used for climate reconstruction from ice cores. The different heavy isotopes of water such as H2 18 O, H2 17 O or HDO give information about local temperature but also temperature and humidity of water vapour sources. Quantification of these parameters relies on the good knowledge of equilibrium and kinetic isotopic fractionation at each step of the water cycle. One of the strongest limitations when interpreting water isotopes in remote Antarctic ice cores is the formulation of the isotopic fractionation at solid condensation (vapour to ice). This classical formulation also implies a good knowledge of coefficients for equilibrium fractionation and water vapour diffusion in air as well as supersaturation in clouds. The uncertainties associated with these different parameters make the formulation of isotopic fractionation at solid condensation only empirical. Here, we make use (1) of recent development in the measurements of water isotopes in the water vapour through infra-red spectroscopy and (2) of the possibility to measure accurately 17 O-excess of water to test the classical formulation and parameterization of isotopic fractionation at solid condensation. A first experiment involving very strong supersaturation evidences a strong kinetic effect on 17 O-excess at solid condensation, similar to d-excess. It also shows the limits of the classical formulation of water isotopic fractionation during solid condensation estimation at very low temperature. A second experiment performed in a cloud chamber under controlled conditions uses cavity ring down spectrometers (CRDS) to determine the spatial variability of water vapour isotopic composition due to diffusion (kinetic effect) during solid condensation. The spatial variability of water vapour isotopic composition can be relatively well reproduced by the resolution of diffusion toward a cold plate. This preliminary study opens new perspectives to revisit the classical formulation of water isotopic fractionation during solid condensation at very low temperature.